128 White matter fibre loss in Parkinson's disease hallucinations. Issue 6 (27th May 2022) - Zarkali, Angeliki; McColgan, Peter; Leyland, Louise-Ann; Rees, Geraint; Weil, Rimona S
Abstract : Visual hallucinations are common in Parkinson's (PD) and associated with worse outcomes. 1 Neuroim- aging shows widespread but non-specific grey matter atrophy in PD-hallucinations 1 ; white matter (WM) loss may be an earlier, more sensitive marker. To detect WM changes in PD-hallucinations we performed diffusion-weighted imaging in 105 patients with PD (n=86 without hallucinations [PD-non-VH], n=19 with hallucinations [PD-VH]), and 35 controls. We performed whole-brain fixel-based analysis, 2 a novel method that can identify micro- and macro-structural changes at fibre level and examined three measures: apparent fibre density (FD), sensitive to micro-structural changes, fibre bundle cross-section (FC), representing macro-structural changes, combined fibre density and cross-section (FDC). Groups did not differ in age or gender. PD-VH had higher total UPDRS score [63.5±35.6 vs 43.2±20.6 in PD-non-VH, (p=0.003)]; motor scores did not differ. We found macrostructural changes (FC reduction) within the splenium of the corpus callosum and left posterior thalamic radiation in PD/VH. Whilst there were no significant changes in FD, when using the combined FDC metric, we found large reductions within the splenium in PD-VH (>50% reduction compared to PD-non-VH). We demonstrate specific WM tract degeneration affecting posterior thalamic tracts in PD-hallucinations, providing direct mechanistic support for attentional models of visual hallucinations. References: Weil, et al . Visual dysfunction in Parkinson's disease. Brain 2016 Jul 13. Raffelt, et al . Investigating white matter fibre density and morphology using fixel-based analysis. Neu- roimage 2017;144 :58–73. a.zarkali@ucl.ac.uk